The relationship between dietary exposure to persistent organic pollutants from fish consumption and type 2 diabetes among First Nations in Canada - Marushka, Lesya (Can J Public Health, 2021)
OBJECTIVE: We previously examined the associations between dietary dichlorodiphenyldichloroethylene (DDE) and polychlorinated biphenyls (PCBs) intake from fish consumption and type 2 diabetes (T2D) prevalence in Ontario and Manitoba. This study aims to further explore the relationship in a regionally representative sample of First Nations adults living on-reserve across Canada. METHODS: Dietary, health and lifestyle data collected by the cross-sectional First Nations Food, Nutrition and Environment Study (2008–2018) were analyzed. This participatory study included 6091 First Nations adult participants who answered questions on T2D. The consumption of locally caught fish was estimated with a food frequency questionnaire. A total of 551 samples from 96 fish species were collected and analyzed for the presence of DDE and PCBs. The associations between fish and dietary DDE/PCBs intake with self-reported T2D were investigated using multiple logistic regression models adjusted for confounders. RESULTS: Dietary exposure to DDE (>2.11 ng/kg/bw) and PCBs (>1.47 ng/kg/bw) vs no exposure was positively associated with T2D with ORs of 2.33 (95% CI: 1.24–4.35) for DDE and 1.43 (95% CI: 1.01–3.59) for PCBs. The associations were stronger among females (DDE OR = 3.11 (1.41–6.88); PCBs OR = 1.76 (1.10–3.65)) and older individuals (DDE OR = 2.64 (1.12–6.20); PCBs OR = 1.44 (1.01–3.91)) as compared with males and younger participants. Also, significant dose-response relationships were found for fish consumption in females only. CONCLUSION: This study confirms our previous findings that dietary DDE/PCBs exposure may increase the risk of T2D. The effect of DDE/PCBs from fish consumption is driven by geographical differences in DDE/PCBs concentrations in fish and by the amount of fish consumed, and is more prominent in females than in males.